UPAYA MENINGKATKAN MINAT DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI OPERASI HITUNG PERKALIAN MELALUI METODE JARIMAGIC DI KELAS II SD NEGERI LAM URA KABUPATEN ACEH BESAR - Maulidar Maulidar (JURNAL TEMATIK, 2015)
Efforts to Increase Interest and Skill Problem Solving Math Students to Content Multiplication Operation Count Numbers Through Jarimagic Method in Class II Elementary School Lam Ura-Large of Aceh district ".Tesis. Terrain: Graduate Program, State University of Medan in 2015. This study aims to: (1) Increase student interest, (2) Improve the ability of students' mathematical problem solving (3) Knowing mastery learning students using jarimagic. This research is conducted in a class action class II Elementary School Lam ura-Large of Aceh with the number of students as many as 20 people. Instruments used to collect the data consists of mathematical problem solving ability test, observation sheet student activity and the ability of teachers to manage learning, observation sheet on student interest. The results showed: (1) learning with Jarimagic method can improve students' mathematical problem solving. For classical class on the first cycle of 72.8% in the first meeting and 75.3% in the second meeting, on the second cycle into 80.05% in the first meeting and 84.3% in the second meeting, (2) learning methods jarimagic can increase student interest, for observation scores increased from 70.1% interest in the first cycle to 84% in the second cycle, (3) the application of learning with jarimajic method for effective mathematics learning process, marked by the achievement of (i) the classical completeness of 85 % above the defined criteria, namely 80%, and an average grade of 82.2 above the defined criteria, namely 80%, (ii) the percentage of student activity both categories of 78.6% in the first meeting and the second meeting of 83.9% in the second cycle, to the ability of teachers to manage learning by 85.1% above the defined criteria, namely 80%, (ii) time-efficient, where the application of learning has been implemented in accordance with the time on RPP.Rekomendasi on the results of this study are the teachers to implement jarimagic learning method as an alternative effort to increase interest and solving mathematical problems students especially in arithmetic operations of multiplication material.